The reform of vocational curricula : outcomes of the 2005 ETF peer reviews in Bulgaria, Bosnia and Herzegovina, the Former Yugoslav Republic of Macedonia, and Serbia - Parkes, David [Verfasser]; Nielsen, Søren [Verfasser] (Office for Official Publications of the European Communities, 2006)
"This publication presents a synthesis of the outcomes of VET specialists from four South Eastern European countries reviewing curriculum policy and actual practice across their own region. The resulting conclusions and recommendations echo Francis Fukuyama's challenge to conventional donor wisdom (including the EU) concerning the relationship between local ownership and practice and assumed external 'best practice' (Fukuyama, State Building, 2005)." (Editor, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 2.2.2 Osteuropa; Berufsbildungssystem; Berufsbildungspolitik; Bildungsreform; Curriculumreform; Arbeitsmarkt; Osteuropa; Bulgarien; Bosnien-Herzegowina; Jugoslawien; Mazedonien; Serbien